Genetics of tumor metastasis 1 - Weinberg, Robert (Henry Stewart Talks, 2015)
Understanding carcinoma invasion and metastasis, Epithelial-mesenchymal transition (EMT), Heterotypic signals in tumor growth and progression, EMT-inducing transcription factors, Transgenic model of breast cancer pathogenesis